The Effect of Corporate Social Responsibility (CSR), Customer Trust, and Customer Satisfaction on Customer Loyalty at PT. Kiat Ananda Group Surabaya - Lie, Steven; Hermeindito, Hermeindito; Santoso, Wiliam (Journal Research of Social Science, Economics, and Management, 2025)
PT. Kiat Ananda Group is a company engaged in the logistics and cold chain industry that focuses on the distribution of products that require strict temperature control. Program Corporate Social Responsibility (CSR) PT. Ananda Group's tips show a positive correlation between CSR initiatives and increased customer satisfaction and loyalty. More active customer engagement in CSR programs, facilitated through innovative and personalized communication campaigns, has the potential to significantly increase the company's sales. By strengthening the emotional bond between customers and brands, companies can build a loyal customer base and drive long-term sales increases. This study aims to analyze the influence of CSR, customer trust, and customer satisfaction on customer loyalty at PT. Tips from Ananda Group Surabaya. This study uses a quantitative method with a random sampling technique and involves 100 respondents of PT. Tips from Ananda Group Surabaya. Primary data is collected through questionnaires to ensure the relevance and accuracy of the information. Data analysis was carried out using a statistical approach using SmartPLS 3.0 to test the proposed hypothesis. Through quantitative/statistical data analysis, this study seeks to test the proposed hypothesis and provide recommendations that can be used by PT. Ananda Group Surabaya's tips to increase their customer loyalty. The results of the study show that: (1) CSR has a positive and significant influence on customer loyalty, (2) customer trust has a positive and significant influence on customer loyalty, (3) customer satisfaction does not have a significant effect on customer loyalty.